The Influence of Brand Awareness, Brand Association, Brand Image, and Word of Mouth on Samsung Smartphone Purchase Decisions - Arienda Gitty Ramadani; Erny Rachmawati (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this research was to determine the effect of brand awareness, brandassociation, brand image, and word of mouth on purchase decisions. The populations in thisresearch are Banyumas citizen. The sample selection in this study was carried out bypurposive sampling. The samples used in this research are 100 samples. The data analysistechniques used in this research are descriptive statistics analysis, instrument test, classicalassumpsion test, multiple regression analysis, goodness of fit test, and hypothesis testing. Theanalysis result show that brand awareness, brand association, dan brand image has no apositive effect on purchase decisions meanwhile financial experience has effect on purchasedecisions.